MEDIA MASA SEBAGAI INSTRUMEN DIPLOMASI AMERIKA SERIKAT DALAM KASUS INVASI KE IRAK DAN AFGANISTAN - Permadi, Dedy (Scriptura, 2009)
Mass media have significant role on shaping public opinion and image of diplomatic agenda. The control over mass media news enables one to succeed their diplomatic agenda. This paper elaborates the use of mass media in realm of discourse construction, specifically in area of diplomatic. The use of mass media to establish a country's agenda is seen in a case of US intervention to Iraq and Afghanistan. Under Bush's administration, US have succeeded to construct public discourse to gain support for the intervention. By the use of widespread coverage of mass media, the administration delivered a discourse of the intervention role in order to maintain the peace of the world.